1997
DOI: 10.1021/jf9609136
|View full text |Cite
|
Sign up to set email alerts
|

Nonchemical Approach for Reducing Antinutritional Factors in Rapeseed (Brassica campestrisVar. Toria) and Characterization of Enzyme Phytase

Abstract: Antinutritional factors, viz. glucosinolates, phenols, and phytic acid, decreased with germination of rapeseed. Protein content declined during the first 24 h after imbibition and thereafter increased. Phytase activity increased with germination with a parallel decrease in phytic acid content. Two phytase fractions were separated during elution on DEAE-cellulose column, showing purifications of 26.75- and 19.96-fold, respectively. Optimum pH and temperature for both fractions were 5.2 and 50 °C, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…As shown in Fig. 2, both vanadate and molybdate are strong inhibitors, as reported for phosphatases and related enzymes (Lindqvist et al, 1994;Mahajan and Dua, 1997;Stankiewicz and Gresser, 1988;Vescina et al, 1996), whereas tungstate has little influence on the hydrolysis reaction and selenate is not an inhibitor. Inhibition constants (K i ) were calculated at 3.9 and 9.4 M, respectively, for vanadate and molybdate.…”
Section: Metal Oxoanion-incorporated Phytasesupporting
confidence: 68%
See 1 more Smart Citation
“…As shown in Fig. 2, both vanadate and molybdate are strong inhibitors, as reported for phosphatases and related enzymes (Lindqvist et al, 1994;Mahajan and Dua, 1997;Stankiewicz and Gresser, 1988;Vescina et al, 1996), whereas tungstate has little influence on the hydrolysis reaction and selenate is not an inhibitor. Inhibition constants (K i ) were calculated at 3.9 and 9.4 M, respectively, for vanadate and molybdate.…”
Section: Metal Oxoanion-incorporated Phytasesupporting
confidence: 68%
“…Recently, it was established (Hemrika et al, 1997;Neuwald, 1997) that vanadium chloroperoxidases are structurally closely related to the (membranebound) acid phosphatases, and the apoenzyme of vanadium chloroperoxidase was shown to exhibit phosphatase-like activity. Moreover, vanadate and other transition metal oxoanions are known to be potent inhibitors of acid phosphatases (Lindqvist et al, 1994;Vescina et al, 1996) and the related phytases (Greiner et al, 1997;Mahajan and Dua, 1997) and sulfatases (Stankiewicz and Gresser, 1988). Hence, we reasoned that incorporation of vanadate ion into the active site of these enzymes should produce novel, semisynthetic peroxidases.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that Ca may inhibit phytase activity (Applegate et al, 2003), while some studies have shown that the Ca-to P-ratio (Ca/P) of the diet affects the response to phytase application (Qian et al, 1996a;Liu et al, 2000). However, there is little tangible evidence that Ca directly inhibits exogenous phytase activity, but data on this aspect are conflicting (Mahajan and Dua, 1997). Nevertheless, to improve phytase activity, it is generally recommended to keep Ca levels to a minimum in phytase-supplemented pig and poultry diets, yet without compromising skeletal integrity or growth performance (Selle et al, 2009).…”
Section: Exogenous Microbial Phytasementioning
confidence: 99%
“…Citing Greiner et al (1993), they attributed this to the inhibition of phytase activity by inorganic P, the end-product of phytate hydrolysis. In an in vitro system, Mahajan and Dua (1997) reported that inorganic P (Na 2 HPO 4 ) inhibited rapeseed phytase activity by up to 80.2%. While there is the possibility that inorganic P may inhibit phytase activity presumably, in vivo, this capacity would be diminished by the absorption of phytaseliberated P from the gastrointestinal tract in vivo.…”
Section: Ternary Calcium-protein-phytate Complexesmentioning
confidence: 99%